EXISTING PROBLEMS IN THE DISTRIBUTION OF DUTIES AND FUNCTIONS OF THE EXECUTIVE AUTHORITIES AND THEIR HEADS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article analyzes the functions of the executive authorities and their heads, issues in the distribution of these functions, functions and existing problems in the distribution of this function.